Academic education in Austria - Sinclair, George M. (The University of Edinburgh, 1957)
GENERAL INTRODUCTION. || CHAPTER I BACKGROUND FACTORS: i. Geographical ii. Historical iii. Economic iv. Political v. Authorities. vi. Teachers vii. Parents viii. Educational Theory and Psychology ix. Austrian Character x. Conclusion. || CHAPTER II - MIINISTRY OF EDUCATION AND SUBORlNATE EDUCATIONAL AUTHORITIES || CHAPTER III - PRE-SCHOOL EDUCATION || CHAPTER IV - COMPULSORY EDUCATION (DAS PFLICHTSCHULWESEN): i. Historical ii. The " Volksschule" to-day Iii. The "Hauptschule" iv. Special Schools (Sonderschulen) v. Present Problems vi. Teacher Training || CHAPTER V - ACADEMIC SECONDARY EDUCATION. i. Historical (a) Pre-1848 (b) 1848-1918 1. "Gymnasien-Entwurf" 2. "Realschule" 3. "Realgymnasium" 4. Girls' Schools (c) Post-1918 1. 1918 -1927 2. 1927 -1938 3. 1938 -1945 4. Post-1945 ii. The Present Situation. (a) Statistics. (b) "Unterr.icht" (c) "Erziehung"' (d) Organisation (e) Teachers (i) Problems || CHAPTER VI - "HOCHSCHULEN": i. Introduction ii. Universities iii. Technical Colleges iv. Other "Hochschulen " APPENDIX: TABLE 1: Organization of Elementary and Secondary Schools until 1919 TABLE 2: Proposed Organization of Elementary and Secondary Schools 1922 -27 TABLE 3: Organization of Elementary and Secondary Schools 1927-1934 and after 1945 TABLE 4: "Stundentafel" for Volksschulen TABLE 5: "Stundentafel" for Hauptschulen TABLE 6: "Stundentafel" in Teachers' Training Colleges TABLE 7e: "Stundentafel" for Mittelschulen - Unterstufe TABLE 7b: Stundentafel" for Drittelschulen - Oberstufe || BIBLIOGRAPHY.